A Turkish Version of Children's Emotional Manifestation Scale: Reliability and Validity Assessment - Selver Mete İzci; Bengü Çetinkaya (Galenos Yayinevi, 2020)
Aim:This study aims to determine the reliability and validity of the Turkish version of the Children's Emotional Manifestation scale (T-CEMS).Materials and Methods:The sample of this methodological-type study consisted of 62 children between the ages of 7 and 12 years who presented at the clinic for day surgery.Results:The Content Validity index of the scale is 0.96, and thus, the scale is statistically significant. Internal consistency was found to be between 0.95 and 0.96 using Cronbach's alpha reliability coefficient. These results show that inter-rater reliability is sufficient.Conclusion:T-CEMS is valid and reliable for measuring the emotional reactions of children before stressful medical processes or during the preoperative period.